Abnormal Large-Scale Neuronal Network in High Myopia - Ji, Yu; Shi, Ling; Cheng, Qi; Fu, Wen-wen; Zhong, Pei-pei; Huang, Shui-qin; Chen, Xiao-lin; Wu, Xiao-rong (Frontiers in Human Neuroscience, 2022)
Abstract Aim: Resting state functional magnetic resonance imaging (rs-fMRI) was used to analyze changes in functional connectivity (FC) within various brain networks and functional network connectivity (FNC) among various brain regions in patients with high myopia (HM). Methods: rs-fMRI was used to scan 82 HM patients (HM group) and 59 healthy control volunteers (HC group) matched for age, sex, and education level. Fourteen resting state networks (RSNs) were extracted, of which 11 were positive. Then, the FCs and FNCs of RSNs in HM patients were examined by independent component analysis (ICA). Results: Compared with the HC group, FC in visual network 1 (VN1), dorsal attention network (DAN), auditory network 2 (AN2), visual network 3 (VN3), and sensorimotor network (SMN) significantly increased in the HM group. Furthermore, FC in default mode network 1 (DMN1) significantly decreased, while FC in default mode network 2 (DMN2), default mode network 3 (DMN3), auditory network 1 (AN1), executive control network (ECN), and significance network (SN) have rising and falling parts at the same time. FNC analysis also showed that the network connection between the default mode network (DMN) and cerebellar network (CER) was enhanced in the HM group. Conclusion: Compared with HCs, HM patients showed neural activity dysfunction within and between specific brain networks, particularly in the DMN and CER. Thus, HM patients may have deficits in visual, cognitive, and motor balance functions. Key words: High myopia, resting state network, independent component analysis, functional connectivity, functional network connectivity